Discourse functions of lexical bundles in Indonesian EFL learners’ argumentative essays: A corpus study - Ikmi Nur Oktavianti; Icuk Prayogi (Universitas Syiah Kuala, 2022)
Lexical bundles are functional units that are essential to building texts. However, lexical bundles vary due to some aspects, e.g., nativity, professionalism, text genre, etc. This study explored functional categories of lexical bundles in EFL written production, i.e., argumentative essays, focusing on 3-, 4-, and 5-word sequences employed by English major students in Indonesia. The data were taken from a learner corpus comprising 169 argumentative essays with 87.939 tokens. The lexical bundles were identified by using computerized and manual procedures. The identified bundles were then classified into functional categories and subcategories by Hyland. The results show that all functional categories were identified in the learner corpus proving the importance of those functions in students’ essays. Regarding the distribution, research-oriented bundles are the most frequent bundles in the corpus, while text-oriented bundles are the least frequent. Although all functional categories were found, the structuring signals (a subcategory of text-oriented bundles) were absent in the corpus. Moreover, this study found the gap between tokens and types of each bundle function, indicating the restricted variants of bundles used by the learners. Considering the low frequency of text-oriented bundles, the absence of structuring bundles, and restricted bundles, thus the exposure of more lexical bundles serving multiple functions in writing materials is necessary, especially bundles used for organizing and structuring texts.